2005
DOI: 10.1055/s-2005-836477
|View full text |Cite
|
Sign up to set email alerts
|

Neurological and Psychosocial Outcome after Subarachnoid Haemorrhage, and the Hunt & Hess Scale as a Predictor of Clinical Outcome

Abstract: In a retrospective study, the outcome of 87 patients with ruptured intracranial aneurysm was assessed. Follow-up included neurological examination, grading of the Glasgow Outcome Scale (GOS) of each patient, and answering a psycho-social questionnaire. This questionnaire was answered by the patients themselves or by a relative when the patient was not able to answer. The follow-up was performed more than 12 months after the occurrence of subarachnoid hemorrhage (SAH) in each patient. The psycho-social question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 23 publications
0
11
0
1
Order By: Relevance
“…Cedzich et al [16] found correlations between the GOS and the quality of life; however, in their study they stated that neither the Hunt and Hess scale nor the Fisher scale is a predictor. In our study the Fisher scale does not predict any of the dimensions studied, but in the predictive model of the Vitality dimension the Hunt and Hess scale does intervene.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Cedzich et al [16] found correlations between the GOS and the quality of life; however, in their study they stated that neither the Hunt and Hess scale nor the Fisher scale is a predictor. In our study the Fisher scale does not predict any of the dimensions studied, but in the predictive model of the Vitality dimension the Hunt and Hess scale does intervene.…”
Section: Discussionmentioning
confidence: 90%
“…Other factors that have also been related to poorer quality of life are physical handicap as rated on the Rankin scale [4, 11], the presence of depression [10], age [12, 13], cognitive impairment [14], an incorrect initial diagnosis [15], the Glasgow Outcome Scale (GOS) [16] and sleep problems [17]. The majority of these studies only examined one specific variable, but they did not try to investigate how and to what extent each factor can contribute to the different dimensions of quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Among the SAH‐related variables, we found that the extent of SAH (assessed in the Fisher's grade) is a predictor of QOL. According to Cedzich and Roth () neither the H‐Hs scale nor the Fisher's grade is a predictor of future QOL; however, Hütter et al. () stated the opposite.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have examined incidence of neurological deficits (motor deficiencies and physical changes) and changes in quality of life for aSAH patients after vasospasm, and this research has revealed high proportions of cases in which vasospasm contributed to the onset of such deficits (2,6,19). The deficits included irritability, depression, anxiety, decreased memory performance and reduced speed of information processing, as well as substantial reductions in quality of life.…”
Section: █ Discussionmentioning
confidence: 99%